HPTLC FINGER PRINT ANALYSIS OF PHYTOPHENOLS OF PAEDERIA FOETIDA UNDER DIFFERENT EXTRACTION REGIMEN - M. R. SENAPATI; P. C. BEHERA; P. C. BISOI A. MAITY S. C. PARIJA (The Bioscan, 2013)
To detect and estimate the phenolics and flavonoids of Paederia foetida in different solvents under CP, MAE system and by HPTLC finger print analysis. Phenolic components in chlorophyll free extracts in different solvent groups were qualitatively detected by chemical tests and total polyphenols and flavonoids were quantitatively estimated following standard protocol. Distinct chemo-profile of the components was analyzed by HPTLC technique with CAMAG win CATS planar chromatography manager software. Among two methods of extraction more components of polyphenols were detected and significantly higher (p<0.05) contents of phenolics and flavonoids were estimated in MAE method than CP method. Out of five solvent types, organic solvent mixtures recovered significantly higher polyphenols (p<0.05) and flavonoids (p<0.001) in comparison to aqueous solvent. CP Method exhibits 12, 14, 14, 14 and 16 peaks for Gr-A, B, C, D and E solvents respectively. In MAE method the numbers of peaks in these respective solvent groups are 15, 21, 19, 18 and 22. Phyto-chemicals can be better screened qualitatively and estimated quantitatively in organic solvent extracts under MAE system by HPTLC finger print analysis than the aqueous solvent and CP method. Abbreviations: CP: Cold Percolation, MAE: Microwave-Assisted Extraction, Rf: Retention factor, HPTLC: High Pressure Thin layer Liquid Chromatography.